2023
DOI: 10.3390/atmos14040640
|View full text |Cite
|
Sign up to set email alerts
|

Filtration Kinetics of Depth Filters—Modeling and Comparison with Tomographic Data of Particle Depositions

Abstract: Depth filtration is a widespread technique for the separation of airborne particles. The evolution of the pressure difference within this process is determined to a significant extent by the filter structure. Simulations are an important tool for optimizing the filter structure, allowing the development of filter materials having high filtration efficiencies and low pressure differences. Because of the large number of physical phenomena and the complex structure of filter materials, simulations of the filtrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Hardly any studies in the literature have been published on the particulate accumulation process prior to and during clogging at a single fiber array containing polydisperse materials. Previous studies focused on the overall filtration performance in a complete filter [23][24][25][26][27]. To conduct these observations, the focus should shift from a whole filter medium to a fiber array or a single fiber collector, as Zhang et al suggested [21].…”
Section: Clogging Point and Characteristic Morphology Of Structures O...mentioning
confidence: 99%
“…Hardly any studies in the literature have been published on the particulate accumulation process prior to and during clogging at a single fiber array containing polydisperse materials. Previous studies focused on the overall filtration performance in a complete filter [23][24][25][26][27]. To conduct these observations, the focus should shift from a whole filter medium to a fiber array or a single fiber collector, as Zhang et al suggested [21].…”
Section: Clogging Point and Characteristic Morphology Of Structures O...mentioning
confidence: 99%